2023
DOI: 10.1038/s41389-023-00471-5
|View full text |Cite
|
Sign up to set email alerts
|

miR-137–LAPTM4B regulates cytoskeleton organization and cancer metastasis via the RhoA-LIMK-Cofilin pathway in osteosarcoma

Abstract: Osteosarcoma (OS) is a rare malignant bone tumor but is one leading cause of cancer mortality in childhood and adolescence. Cancer metastasis accounts for the primary reason for treatment failure in OS patients. The dynamic organization of the cytoskeleton is fundamental for cell motility, migration, and cancer metastasis. Lysosome Associated Protein Transmembrane 4B (LAPTM4B) is an oncogene participating in various biological progress central to cancer biogenesis. However, the potential roles of LAPTM4B in OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To generate LAPTM4B knockout (KO) cells, the CRISPR/Cas9n system was employed, following a previously established methodology [ 23 , 30 ]. In brief, the coding sequences in exon 3 of LAPTM4B (Gene ID: 55353) were analyzed, and Cas9 nickase targets were designed ( http://crispr.mit.edu ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate LAPTM4B knockout (KO) cells, the CRISPR/Cas9n system was employed, following a previously established methodology [ 23 , 30 ]. In brief, the coding sequences in exon 3 of LAPTM4B (Gene ID: 55353) were analyzed, and Cas9 nickase targets were designed ( http://crispr.mit.edu ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, LAPTM4B stimulates cancer cell stemness [ 17 ], autophagy [ 20 ], and drug resistance [ 21 ]. Mechanistically LAPTM4B can regulate cancer progression via several pathways: LAPTM4B promotes integrin beta1 recycling and regulate cytoskeleton organization, thus enhances cell migration [ 22 , 23 ]; It regulates drug resistance via the PI3K-AKT pathway [ 24 ], stimulates tumor growth via activating mTORC1 signaling [ 25 ], and regulates cell growth and autophagy though prolonging EGFR signaling [ 26 , 27 ]. We have shown that LAPTM4B interacts with ceramide [ 28 , 29 ] which promotes its interaction with the leucine transporter SLC3A2/SLC7A5, stimulating lysosomal leucine uptake and the downstream mTORC1 signaling [ 30 ], which is in agreement with the finding by Milkereit et al that LAPTM4B recruits SLC3A2 into lysosome and promotes mTORC1 activity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…
Editorial on the Research Topic Functional screening for cancer drug discovery: from experimental approaches to data integration Cancer is still one of the leading causes of death worldwide, despite that tremendous resources are being invested in drug discovery (Siegel et al, 2022). Recent developments in uncovering the molecular biology of oncogenesis and tumor development (Zhou et al, 2018; Liu M. et al, 2022;Yan et al, 2023), and the studies on cancer polypharmacology (Pushpakom et al, 2019;Cohen et al, 2021) have challenged researchers to come up with new strategies for integrating ever-growing data at the molecular levels.The majority of cancer medications consist of small molecule inhibitors. These inhibitors are engineered to enhance their efficacy by binding to specific cellular protein targets, which in turn initiate a series of downstream changes in cancer signaling and metabolic pathways (Yang et al, 2019;Goel et al, 2020).
…”
mentioning
confidence: 99%
“…Editorial on the Research Topic Functional screening for cancer drug discovery: from experimental approaches to data integration Cancer is still one of the leading causes of death worldwide, despite that tremendous resources are being invested in drug discovery (Siegel et al, 2022). Recent developments in uncovering the molecular biology of oncogenesis and tumor development (Zhou et al, 2018; Liu M. et al, 2022;Yan et al, 2023), and the studies on cancer polypharmacology (Pushpakom et al, 2019;Cohen et al, 2021) have challenged researchers to come up with new strategies for integrating ever-growing data at the molecular levels.…”
mentioning
confidence: 99%